2020
DOI: 10.3897/mycokeys.66.48711
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Neotropical tree pathogens in Moniliophthora: a new species, M. mayarum, and new combinations for Crinipellis ticoi and C. brasiliensis

Abstract: The crinipelloid genera Crinipellis and Moniliophthora (Agaricales, Marasmiaceae) are characterized by basidiomes that produce long, dextrinoid, hair-like elements on the pileus surface. Historically, most species are believed to be saprotrophic or, rarely, parasitic on plant hosts. The primary morphological diagnostic characters that separate Crinipellis and Moniliophthora are pliant vs. stiff (Crinipellis) stipes and a tendency toward production of reddish pigments (ranging from violet to orange) in the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For instance, Evans et al ( 2002 ) suggested placement of the frosty pod rod, Moniliophthora roreri , an important pathogen on cacao, in the genus Crinipellis , based on the notion that its ITS sequence blasted most closely to Crinipellis perniciosa . Subsequent phylogenetic analysis, however, demonstrated that the latter was not a genuine Crinipellis but formed a separate generic lineage together with Moniliophthora roreri in Marasmiaceae (Aime and Phillips-Mora 2005 ; Kerekes and Desjardin 2009 ; Evans 2016 ; Niveiro et al 2020 ).…”
Section: Species: From Concepts To Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Evans et al ( 2002 ) suggested placement of the frosty pod rod, Moniliophthora roreri , an important pathogen on cacao, in the genus Crinipellis , based on the notion that its ITS sequence blasted most closely to Crinipellis perniciosa . Subsequent phylogenetic analysis, however, demonstrated that the latter was not a genuine Crinipellis but formed a separate generic lineage together with Moniliophthora roreri in Marasmiaceae (Aime and Phillips-Mora 2005 ; Kerekes and Desjardin 2009 ; Evans 2016 ; Niveiro et al 2020 ).…”
Section: Species: From Concepts To Identificationmentioning
confidence: 99%
“…the various forms of endophytes, lichens and mycorrhizae. Fungi have economic impact as plant and animal (including human) pathogens, in the biological control of crop pests, in the food and pharmaceutical industry, as edible mushrooms, and are also applied as indicators of environmental health (May and Adams 1997;Nimis et al 2002;Crawford 2019;Hyde et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these genes were shown to be highly expressed during the biotrophic interaction of M. perniciosa and cacao, suggesting that MpPR-1 proteins have important roles during this stage of WBD. M. perniciosa has two other known biotypes (S and L) that differ in host specificity and virulence, the closest related species M. roreri that also is a T. cacao pathogen, and other nine Moniliophthora species: one described as a nonpathogenic grass endophyte (Aime & Phillips-Mora, 2005), three of biotrophic/parasitic habit (Niveiro et al, 2020), and five species of unascertained lifestyle, found in dead or decaying vegetal substrates (Kerekes et al, 2009;Kropp & Albee-Scott, 2012;Takahashi, 2002). Accelerated adaptive evolution evidenced by positive selection signs has also been observed in other virulence-associated genes of pathogenic fungi, such as the genes PabaA, fos-1, pes1, and pksP of Aspergillus fumigatus, which are involved in nutrient acquisition and oxidative stress response (Fedorova et al, 2008), and several gene families in C. albicans, including cell surface protein genes enriched in the most pathogenic Candida species (Butler et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…M. perniciosa has two other known biotypes (S and L) that differ in host specificity and virulence, the closest related species M. roreri that also is a T. cacao pathogen, and other nine Moniliophthora species: one described as a nonpathogenic grass endophyte (Aime & Phillips-Mora, 2005), three of biotrophic/parasitic habit (Niveiro et al, 2020), and five species of unascertained lifestyle, found in dead or decaying vegetal substrates (Kerekes et al, 2009;Kropp & Albee-Scott, 2012;Takahashi, 2002). Because the majority of Moniliophthora related fungi in the Agaricales order are saprotrophs, the occurrence of parasitic Moniliophthora species raises the question about the emergence of biotrophic/parasitic lifestyle in this lineage of Marasmiaceae (Niveiro et al, 2020;Teixeira et al, 2015). The evolutionary scenario of host-pathogen arms race that emerges through the diversification of the Moniliophthora genus in the Agaricales order and of host-specific biotypes in M. perniciosa isolates, is especially suitable for the study of adaptive evolution in pathogenicity-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation